Correlation between serum autotaxin levels and optic neuropathy in early diabetic retinopathy: a case-control study - Chen, Wenjun; Chen, Xiaori; Wang, Yaming; Guo, Chuanheng; Yu, Shaowen; Zhao, Wen (Frontiers in Medicine, 2025)
ObjectiveTo explore the correlation between serum autotaxin (ATX) levels and optic neuropathy in early diabetic retinopathy (DR).MethodsA total of 90 patients with early DR who were treated in our hospital from August 2022 to December 2023 were selected as the Non diabetic neuropathy (NDN) group, and another 90 patients with early DR combined with optic neuropathy were selected as the combined diabetic neuropathy (DN) group. In addition 90 healthy patients were selected as a normal control group. The general data of the two groups of patients were collected, and the levels of inflammatory factors were compared, including the platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), systemic inflammation response index (SIRI), platelet-to-albumin ratio (PAR), serum C-reactive protein (CRP), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6). The levels of ATX, glial fibrillary acid protein (GFAP), and neurofilament light chain protein (NfL) were also compared between the two groups. Retinal OCT examination was performed in both groups to record the foveal avascular zone (FAZ) area, acircularity index (AI), mean RNFL thickness at the disk margin, temporal, superior, nasal, and inferior, and mean macular ganglion cell inner plexiform layer (mGCIPL) thickness and vascular density (VD) levels. Pearson analysis was used to analyze the correlation between ATX and inflammatory factors, GFAP, NfL, mGCIPL, and VD levels. Multivariate Logistic regression analysis was used to analyze the influencing factors of optic neuropathy in DR patients. ROC curve analysis was used to analyze the clinical value of ATX in diagnosing optic neuropathy in DR patients.ResultsThere were no significant differences in PLR, NLR, LMR, PAR, SIRI index, serum TNF-α, CRP, and IL-6 levels between the healthy group, the NDN group and the combined DN group (P > 0.05). However, serum ATX, GFAP, and NfL levels in the combined DN group were significantly higher than those in the healthy group and the NDN group, and the difference was statistically significant (P < 0.05). The mGCIPL and VD levels of the combined DN group were significantly lower than those of the healthy group and the NDN group, and the difference was statistically significant (P < 0.001). Pearson correlation analysis showed that the ATX level of DR patients was positively correlated with GFAP and NfL (P < 0.05), and negatively correlated with mGCIPL and VD levels (P < 0.001). The results of multivariate logistic regression analysis showed that serum ATX, GFAP, and NfL levels were independent risk factors for optic neuropathy in DR patients (P < 0.05), and GFAP and NfL were independent protective factors (P = 0.001). The results of ROC curve analysis showed that the area under the curve (AUC) of ATX for diagnosing optic neuropathy in DR patients was 0.873, with a 95% CI of 0.808–0.938. When the ATX cut-off value was 4.69 ng/mL, the maximum Youden index was 0.635, with a sensitivity of 71.11% and a specificity of 93.33%. It has certain clinical value in diagnosing optic neuropathy in DR patients.ConclusionThe increase of serum ATX content may be involved in the occurrence and development of optic neuropathy in DR, and has a significant correlation with early neurological and vascular changes in the early stage of the disease. Measuring serum ATX levels may aid in the early diagnosis of optic neuropathy in DR and provides new ideas for its treatment.